Studi Eksperimen Penerapan Cat pada Plywood dengan Kuas - Lidia Gunawan; Andereas Pandu Setiawan (Intra, 2014)
The needs of plywood as industrial raw materials increased along with the development of the usefulness of plywood in human life. This study took the subject of experimental of paint finishing with brush that is applied to the plywood. In wood process, finishing is a very important stage. Finishing process is commonly known as paint application process. Type of paint is varied, depends on the constituent materials, usability to location of use. Type of paint chosen in this study is oil paint, duco, latex, acrylic, and epoxy This research using qualitative and quantitative methods in which this research aims to know the character (power test viscocity, ,adhesive potensial, gloss intensity and dry resources) each type of paint on the deployment process of paint on plywood with a brush, as well as find out the most suitable type of paint applied to plywood epoxy paint which is obtained from the results of testing.